Editorial: maintaining open access to high quality publications at no cost to authors - Barbara R Conway; Hamid A Merchant (University of Huddersfield Press, 2017)
The inability to access scientific literature freely can be a major obstacle in the advancement of science. Many reputable journals offering optional open access incur a substantial upfront payment to cover their publication costs, and hence many authors cannot afford to publish open access papers in a journal with an established reputation. Publishers charging for article processing claim that the charge is necessary to maintain their reputation and costs for peer review, editing and indexing articles. Thus, some open-access publications have a less rigorous peer-review and editorial process.